Informasi Konten Sportainment TEPOK BULU’23 Pada Youtube Vindes Terhadap Sikap Viewers - Imtiyaz Yasmin; Funny Mustikasari Elita; Yuliani Dewi Risanti Sunarya (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
This study aims to determine the effect of TEPOK BULU'23 sportainment content information on YouTube Vindes on viewers' attitudes. TEPOK BULU'23 sportainment content information on YouTube Vindes to shape viewers' attitudes towards badminton. The information component is divided into two, namely information valence and information weight. This research uses quantitative methods with data collection techniques, namely using questionnaires in the form of Google Forms and literature studies as research references. The population in this study was 115 and calculated using the Slovin formula, a research sample of 90 respondents was obtained. The sampling technique used in this study was simple random sampling. The analysis used in this research is descriptive analysis and inferential analysis, which is processed through the IBM SPSS Statistics application. The results of this study indicate that simultaneously TEPOK BULU'23 sportainment content information on YouTube Vindes (X) has a significant effect on the attitude of viewers (Y). Then, partial testing for the information valence sub variable (X1) has a significant effect on the viewers' attitude (Y), while the information weight sub variable (X2) has no significant effect on the viewers' attitude (Y).